2017
DOI: 10.1016/j.jsat.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Documented brief intervention not associated with resolution of unhealthy alcohol use one year later among VA patients living with HIV

Abstract: Objective Unhealthy alcohol use is particularly risky for patients living with HIV (PLWH). Brief interventions reduce drinking among patients with unhealthy alcohol use, but whether its receipt in routine outpatient settings is associated with reduced drinking among PLWH with unhealthy alcohol use is unknown. We assessed whether PLWH who screened positive for unhealthy alcohol use were more likely to resolve unhealthy drinking one year later if they had brief alcohol intervention (BI) documented in their elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…Other studies evaluating measures of alcohol use severity before and after participating in SBIRT show similar results [ 41 ]. A more recent study among PLHIV, however, found that although alcohol use declined over time, the decline was not associated with receipt of a brief intervention [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies evaluating measures of alcohol use severity before and after participating in SBIRT show similar results [ 41 ]. A more recent study among PLHIV, however, found that although alcohol use declined over time, the decline was not associated with receipt of a brief intervention [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis found little evidence that SBIRT increased patients’ receipt of care to reduce alcohol consumption [ 23 ]. A more recent study found no association between a brief intervention and resolution of alcohol use disorder at follow-up in PLHIV patients of the VA [ 24 ]. A qualitative study sought to identify facilitators and barriers to implementing SBIRT in primary care, and found general patient support for SBIRT, but also identified inconsistent implementation and provider lack of time as barriers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol SBI . The primary measure of alcohol SBI requires that a patient who has a PC visit has screened positive for unhealthy alcohol use on the day of the visit or in the past year (AUDIT-C ≥ 3 for women and ≥ 4 for men) and has a brief intervention documented on the day of the visit or in the following 14 days [ 48 ]. Our indicator of brief intervention is a composite measure based on two data sources: NLP and ICD codes.…”
Section: Methodsmentioning
confidence: 99%
“…Although implementation of alcohol SBI in the VA increased patient report of receiving alcohol-related advice [ 43 ], it also had limitations. The VA implementation strategies resulted in variable-quality screening [ 44 , 45 ], incomplete understanding and “ownership” of preventive alcohol-related care among front-line primary care (PC) staff [ 46 ], and unclear benefits in reducing consumption among patients [ 47 , 48 ]. Moreover, biased denominators may have impacted performance monitoring [ 45 , 49 ], and incentives to document brief intervention may have led to increased EHR documentation of brief intervention that was already occurring [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 However, patients with HIV, who often report other substance use in addition to alcohol, 12 may require more extensive interventions. 13 To address this gap, the Health and Motivation Study compared usual care with two promising interventions to reduce unhealthy alcohol use and comorbid drug use, provided as a supplement to systematic SBIRT, within a large HIV primary care clinic.…”
Section: Introductionmentioning
confidence: 99%